Peningkatan Kapasitas Pengelolaan Badan Usaha Milik Desa (BUMDES) Di Kecamatan Sagaranten Kabupaten Sukabumi - Gilang Rahmadani; Yana Fajar Basori; Dine Meigawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This research is entitled "Improving the Management Capacity of Village Owned Enterprises (BUMDES) in Sagaranten District, Sukabumi Regency". The purpose of this study is to explain the capacity building of a public organization, namely a village-owned enterprise (BUMDES). Most BUMDes in Sagaranten sub-district seem to be just joining in or being talkative, which is when the BUMDes institutions and management have been established, but the potential that exists in their village areas has not been explored. So that after the formation of BUMDes, they cannot create business units or programs to utilize the potential of their own village, to provide benefits in accordance with the principles and objectives of BUMDes to the local community. The theory used to measure an increase in the capacity of an organization is the theory of capacity building written by Marilee S. Grindle (1997). The method used in this research is descriptive qualitative research method. Data collection techniques were carried out through observation, interviews and documentation. The results of this study indicate that the mobilization carried out in carrying out business activities has not been maximized, and the control is not optimal. Because some of the planned business programs are not in accordance with the potential that exists in the village. Thus, the management of BUMDes has not been running and achieving its objectives according to the BUMDes principles. Keywords : Capacity Building, Village Owned Enterprises,